Randomized controlled trial of 'teens and toddlers': A teenage pregnancy prevention intervention combining youth development and voluntary service in a nursery. Issue 5 (31st July 2013) - Bonell, Chris; Maisey, Ruth; Speight, Svetlana; Purdon, Susan; Keogh, Peter; Wollny, Ivonne; Sorhaindo, Annik; Wellings, Kaye
ABSTRACT: We conducted an independent evaluation of the "Teens and Toddlers" intervention. Our randomized trial examined effects on self‐reported last sex without contraception, >1 episode of sex without contraception in previous 3 months, expectation of teenage parenthood and youth development score, plus secondary outcomes among 449 at‐risk girls age 13/14 in England. The intervention involves 18–20 weekly sessions in pre‐school nurseries. Response rates were 95% post‐intervention and 91% one year later. At follow‐up two, there was no evidence of intervention benefits for primary outcomes and a positive impact for our secondary outcome, low self‐esteem. At follow‐up one, there was no evidence of benefits for our primary outcomes but evidence of benefits for our secondary outcomes: low self‐esteem; low sexual health knowledge; and difficulty discussing the contraceptive pill. The intervention should be refined, with a clearer logic model and more emphasis on sex education, and re‐evaluated.